2009
DOI: 10.1007/s11069-009-9458-0
|View full text |Cite
|
Sign up to set email alerts
|

An examination of rip current fatalities in the United States

Abstract: This study analyzes fatalities caused by rip currents in the conterminous United States for the period 1994-2007. Results include the frequency of fatalities from rip currents, their cause, and their unique spatial distributions. An analysis of historical hazard event data illustrate that, on average, 35 people reportedly die from rip currents each year in the United States. Also, similar to other hazard events where unique differences in gender vulnerability have been found, men are over six times more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 12 publications
2
58
0
1
Order By: Relevance
“…Klein et al, 2003;Sherker et al, 2008;Gensini and Ashley, 2010;Scott et al, 2009;Brander et al, 2011). These strong, narrow seaward-flowing currents occur on any beach characterised by waves breaking across a wide area and can occur during conditions of both low and high wave energy conditions on many different types of beaches (Short, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Klein et al, 2003;Sherker et al, 2008;Gensini and Ashley, 2010;Scott et al, 2009;Brander et al, 2011). These strong, narrow seaward-flowing currents occur on any beach characterised by waves breaking across a wide area and can occur during conditions of both low and high wave energy conditions on many different types of beaches (Short, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the United States it is widely reported by the United States Lifesaving Association (USLA) that the annual number of fatalities due to rip currents exceeds 100 (Brewster, 2010) and Lushine et al (1999) estimated this number to be closer to 150. However, using an analysis of historical hazard event data, Gensini and Ashley (2010) suggested that on average 35 people die from rip currents each year in the US. The discrepancy in these estimates is significant and, depending on which estimate is reported by the media, may have implications towards the perceived severity of the hazard to the general public, the funding and sponsorship of valuable rip current public education programs, and the provision of lifeguarding services A similar situation exists in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that these values are likely under-estimated given that accurate incident reporting of rip current drowning is difficult and many beach drowning due to unknown causes are likely due to rip currents. Gensini and Ashley (2010) describe a similar scenario for rip current drowning fatalities in the United States. For this reason, we simply do not know the actual number of people who drown in rip currents globally, although Fletemeyer and Leatherman (2010) estimate that the annual number exceeds 1000.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…For example, based on an analysis of natural hazard and media report databases, Gensini and Ashley (2009) suggested that an average of 35 people per year drown in rip currents on beaches in the United States. This is in contrast to the commonly reported approximate value of 100 by the United States Lifesaving Association (USLA; Brewster, 2010) and 150 reported by Lushine (1991).…”
Section: Introductionmentioning
confidence: 99%